Overseas Experience of Introducing Advanced Technologies of Production System Upgrading - S. B. Baurina; N. B. Akulenko (Вестник Российского экономического университета имени Г. В. Плеханова)
Today's enterprise in order to be competitive needs not only to use high technologies, put out science-intensive products and have the R & D department with high innovation potential. To response in good time and adequately to challenges called 'digital economy' the company will be able only if it possesses a flexible adaptive production system providing synergy to all divisions, all employees of the enterprise. This system should continuously upgrade not to lose its relevance. The article deals with methodology of '20 keys' as an integrator of well-known approaches to enhancing the organization work. Its specific features and advantages were identified, as well as concrete results of introducing this methodology by overseas companies, in particular, the American company 'Windfall Products' specializing in production of powder metal components. The system of five-level appraisal of the organization formulated in the company is introduced in the article. Key stages of reforming conducted in the company, concrete processes and steps being in line with each of the stages are described there. Benefits of the program of '20 keys' for realizing modern tools and approaches to business enhancement are also included in the article.